A dual role of cholesterol in osteogenic differentiation of bone marrow stromal cells. Issue 3 (14th October 2018) - Li, Kun; Xiu, Chunmei; Zhou, Qiang; Ni, Li; Du, Jun; Gong, Tingting; Li, Meng; Saijilafu,; Yang, Huilin; Chen, Jianquan
Abstract: Osteoblasts, the chief bone‐forming cells, are differentiated from mesenchymal stromal/stem cells. Disruption of this differentiation process can cause osteoporosis, a bone disease characterized by low bone mass and deteriorated bone structure. Cholesterol has been implicated in pathogenesis of osteoporosis, and was recently identified as an endogenous activator of Hedgehog (Hh) signaling. However, its pathological and physiological roles in osteoblast differentiation are still poorly understood. Moreover, it is unclear whether these potential roles played by cholesterol are related to its capability to modulate Hh pathway. In this study, we investigated the role of exogenous versus endogenous cholesterol in osteogenesis and Hh pathway activation using ST2 cells, a bone marrow stromal cell line. We found that exogenous cholesterol significantly inhibited alkaline phosphatase (ALP) activity and messenger RNA expression of osteoblast markers genes ( Alpl, Sp7, and Ibsp ) while modestly activating expression of Gli1 (a readout of Hh signaling) under both basal osteogenic culture condition and Wnt3a treatment. Similarly, exogenous cholesterol suppressed osteogenic response of ST2 cells to sonic Hh (Shh) or purmorphamine (Purmo) treatment, which, however, was accompanied by diminished induction of Gli1, indicating the involvement of a Hh‐dependent mechanism. Interestingly, depletion of endogenous cholesterol also reduced Shh‐induced ALP activity and Gli1 expression. Likewise, cholesterol depletion inhibited osteogenic response to Purmo, although it did not affect Gli1 induction. Taken together, our findings have demonstrated that cholesterol plays a dual role in osteoblast differentiation likely through both Hh‐dependent and ‐independent mechanisms. Abstract : Exogenous cholesterol inhibits osteoblast differentiation of bone marrow stromal cells (BMSCs). Endogenous cholesterol is required for osteogenic response of BMSCs to Hedgehog (Hh) signaling. Cholesterol modulates osteogenic differentiation of BMSCs probably through both Hh‐dependent and ‐independent pathways